TALIGITAR: Innovative Media in Increasing Elementary School Students' Learning Interest: - Alfita , Fadtma; Jumadi; Avita, Dwi; Azzam, Ahmad (Universitas Pendidikan Ganesha, 2024)
The research examines the problem of the relatively low level of learning interest of grade 6 students, especially in the context of learning mathematics, especially multiplication and division. This research aims to develop TALIGITAR (Smart Mathematics Multiplication and Division Tables) to increase students' interest in mathematics. This type of research is Research and Development (R&D) using the ADDIE development method. The research subjects are material experts and learning media experts. The test subjects were grade 6 students. The methods used to collect data were observation, interviews and questionnaires. The data collection instrument is a questionnaire. The techniques used to analyze data are qualitative descriptive analysis and quantitative descriptive analysis. The research results, namely the assessment from material experts, reached a percentage of 76% with suitable criteria. Media experts achieved a percentage of 80% with good criteria. The trial results on grade 6 students showed a percentage of 78% with good criteria. It was concluded that overall,